ANALYSIS OF THE INFLUENCE OF CURREN RATIO, RETURN ON ASSETS, RETURN ON EQUITY, NET PROFIT MARGIN, AND DEBT TO EQUITY RATIO ON STOCK RETURNS OF LQ 45 COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2021 - Maria Veronika Dora Wesso; Stanis Man; Henny A. Manafe (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study was to find out: 1) The partial significance of the influence of the curren ratio, return on assets, return on equity, net profit margin, and debt to equity ratio variables on stock returns of LQ 45 companies listed on the Indonesia Stock Exchange in 2019-2021. 2) The significance of the simultaneous influence of the curren ratio, return on assets, return on equity, net profit margin, and debt to equity ratio variables on stock returns of LQ 45 companies listed on the Indonesia Stock Exchange for 2019-2021. This study uses a quantitative method, the samples used in this study are companies that are members of the LQ 45 index on the Indonesia Stock Exchange in 2019-2021, totaling 25 companies. Data were collected using documentation techniques and analyzed using descriptive and inferential statistics using the SPSS 26 application. The results of the inferential analysis show that simultaneously curren ratio, return on assets, return on equity, net profit margin, and debt to equity ratio have a significant effect on stock returns, while partially return on assets and net profit margin have a positive and significant effect on stock returns. current ratio, return on assets and debt to equity ratio have a negative and significant impact on stock returns. The value of R sequare shows that the contribution of curren ratio, return on assets, return on equity, net profit margin, and debt to equity ratio to stock returns is 50.2%, while the rest is influenced by other variables that were not examined in this study.